THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1930)
Abstract The adjustment of the student who has had bookkeeping in secondary school to the college courses in elementary accounting is a troublesome problem. Mingling such students with those who have had no such preliminary work causes disturbances of teaching, and segregating them into separate courses seems to offer just as great difficulties. Probably the larger number of colleges make no distinction in the elementary course between students with a knowledge of bookkeeping and those without. High schools and commercial teachers are of the opinion that the commercial course should either be given preference for admission to schools of business and commerce or that the commercial work lead directly to somewhat more advanced work in the field of business. These teachers frequently look to the schools of business as the goal of their better students and urge them to continue their training. To an increasing extent also the universities are serving as training schools for commercial teachers, and these former students feel their work should be recognized. It is difficult to do this with the usual commercial subjects but it should be possible to make some adjustment for bookkeeping courses since a good deal of such work is necessarily duplicated in our accounting courses.